2015
DOI: 10.1002/ejoc.201501079
|View full text |Cite
|
Sign up to set email alerts
|

Domino Oxidative Cyclization of 2‐Amino­acetophenones for the One‐Pot Synthesis of Tryptanthrin Derivatives

Abstract: A new CuI/DMSO-mediated oxidative domino process has been developed for the synthesis of tryptanthrin derivatives. This is the first example of the synthesis of tryptanthrin deriv-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…These results clearly demonstrated that ionic liquids 1 and 2 are excellent microwave absorbers, and these ionic solvents outperformed the molecular solvent DMF in the one-pot synthesis of tryptanthrin. Moreover, under our experimental conditions, toluene, a commonly used solvent for the synthesis of tryptanthrin, produced no trace of tryptanthrin (entries 8 and 9, Table 1) [19,[22][23][24][25][26][27][28][29][30]. Although poor isolated yields of tryptanthrin were obtained in the ionic liquid 1 and DMF without the use of any base, ionic liquid 1 nevertheless produced a higher tryptanthrin yield than DMF: 19% versus 6%, respectively (entries 6 and 7, Table 1).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…These results clearly demonstrated that ionic liquids 1 and 2 are excellent microwave absorbers, and these ionic solvents outperformed the molecular solvent DMF in the one-pot synthesis of tryptanthrin. Moreover, under our experimental conditions, toluene, a commonly used solvent for the synthesis of tryptanthrin, produced no trace of tryptanthrin (entries 8 and 9, Table 1) [19,[22][23][24][25][26][27][28][29][30]. Although poor isolated yields of tryptanthrin were obtained in the ionic liquid 1 and DMF without the use of any base, ionic liquid 1 nevertheless produced a higher tryptanthrin yield than DMF: 19% versus 6%, respectively (entries 6 and 7, Table 1).…”
Section: Resultsmentioning
confidence: 91%
“…All these intriguing biological activities from tryptanthrin justify the study for its improved synthesis as a useful scaffold for drug discovery and the advanced development as anti-microbial, anti-inflammatory, and anti-neoplastic agents. Many syntheses of tryptanthrin were reportedly achieved under basic and refluxing conditions (e.g., Et3N in refluxing toluene for 16 h) [19,[22][23][24][25][26][27][28][29][30]. As one example, Srinivasan and co-workers reported the two steps synthesis of tryptanthrin in moderate (54%) isolated yield involving the use of LDA and starting from anthranilic acid, methyl anthranilate, and ethyl orthoformate [26].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wang and co-workers proposed a graceful synthesis of tryptanthrins from indoles via the copper-catalyzed aerobic oxidation (Scheme b) . In addition, Reddy and co-workers developed a copper-catalyzed domino oxidative cyclization strategy for the construction of tryptanthrins from 2-aminoaryl methyl ketones and isatins. Herein, we present an ambient-temperature tert -butyl hydroperoxide (TBHP)/K 3 PO 4 -promoted domino oxidative cyclization for the divergent synthesis of quinazolin-4­(3 H )-ones and tryptanthrins (Scheme c).…”
mentioning
confidence: 90%
“…Tryptanthrin, as a kind of natural quinazoline alkaloid, was isolated from the indigo plant Strobilanthes cusia (Acanthaceae) . Various approaches were explored for efficient construction of this significant skeleton because of its widespread biological and pharmaceutical activities . Among these, the oxidative cyclization of isatins or its analogues have received considerable attention in light of the availability of starting materials.…”
mentioning
confidence: 99%
“…Moreover, the reaction of 2‐bromophenyl isocyanide with electrophilic methyl‐2‐isocyanatobenzoate, I 2 ‐tert‐butyl hydroperoxide catalyzed intramolecular amination, insertion of aryne intermediate to quinazolinones and copper catalyzed reaction have been developed for the synthesis of tryptanthrin. Oxidative dimerization of isatin or indole including oxidation of isatin with KMnO 4 , copper catalyzed oxidation of indole, Dakin oxidation of indole‐3‐carbaldehyde and oxone induced oxidation of indole‐3‐carbaldehyde also led to the formation of tryptanthrin.…”
Section: Introductionmentioning
confidence: 99%